Beyond Tang Chang’s Self-Portraits - Nawapooh Sae-tang,; Simon Soon Sien Yong,; Wahyuni Masyidah Md Isa, (Wacana Seni Journal of Arts Discourse, 2025)
This article analyses several self-portraits by Sino-Thai artist Tang Chang, renowned for his abstract paintings and concrete poetry. It examines how these works extend beyond mere self-representation to reflect his views on social roles, family, and the political climate of his time. Self-portraits were a significant part of Chang’s body of work, with over 400 pieces created throughout his life. His self-portraits reveal his deep connection to his family, particularly his close relationship with his wife. They also played a key role in his artistic experimentation and served as teaching tools for his students. Additionally, his most renowned self-portrait in Thai society reflects his response to the political landscape. These self-portraits not only represent his identity but also function as autobiographical narratives, offering deeper insights into his life and beliefs.